(untitled) (Research, Society and Development, 2019)
Burns are very common in Brazil, which is one of the countries in the world where they occur very frequently and that cause environmental damage and human health. In 2017 according to data from INPE, the country broke a record in the amount of these crimes. This article aims to analyze social representations of the Web in cartoons about these types of fires. A field research is carried out in the virtual space, in which objects that meet the characteristics of the study are sought. The cartoons reveal that people are aware of the damage caused by fire, but the country is very large in territorial extension and the burnings are practiced in more unpopulated regions, far from large centers and in these regions the interest is either agribusiness or culture of the region. Land clearing in the old way is still present despite existing legislation.